Policy Implementation Of The On Stop Administration System (Samsat) At The Samsat Office City Of Pematang Siantar - Arief Wibawa Damanik (IHSA Institute, 2020)
The implementation of the policy is a manifestation of the stages of a public policy that has been formulated. The implementation of the one-stop administration system is a service breakthrough in the field of motor vehicle tax. The implementation of the one-stop administration system is required to provide maximum service. smoothly. To answer the research problems, descriptive research methods are used with a qualitative approach. Data collection is done by interview and questionnaire techniques. In addition, data collection is also done by observation and documentation techniques. The data analysis process is carried out by grouping and combining the data obtained and also establishing a series of relationships between the data. Meanwhile, the validity of the data was tested through data sources so that the data presented were valid data. This can be seen from four important points, namely regarding the bureaucratic structure that is clear and directed, the resources that have been fulfilled, good communication and the disposition of the Pematangsiantar City SAMSAT employees and the community who support the existing policies. However, the strategic location of the Pematangsiantar City SAMSAT office is still lacking. Based on data findings in the field, it shows that the implementation of motor vehicle tax services at the SAMSAT Office of Pematangsiantar City has been implemented. This can be seen from four important points, namely regarding the bureaucratic structure that is clear and directed, the resources that have been fulfilled, good communication and the disposition of the Pematangsiantar City SAMSAT employees and the community who support the existing policies. However, the strategic location of the Pematangsiantar City SAMSAT office is still lacking. Based on data findings in the field, it shows that the implementation of motor vehicle tax services at the SAMSAT Office of Pematangsiantar City has been implemented. This can be seen from four important points, namely regarding the bureaucratic structure that is clear and directed, the resources that have been fulfilled, good communication and the disposition of the Pematangsiantar City SAMSAT employees and the community who support the existing policies. However, the strategic location of the Pematangsiantar City SAMSAT office is still lacking.